INFLUENCE OF PURE AND Cd, Zn DOPED CuO THIN FILMS USING SPRAY PYROLYSIS TECHNIQUE - S. J. Helen, R. Chandramohan, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Pristine (undoped) and Zinc, Cadmium doped CuO thin films are prepared using spray pyrolysis technique over glass substrates. Influence of Zn andf Cd doping on the structural, optical and electrical properties of CuO thin films is reported. X ray diffraction (XRD) analysis exposes that the prepared pure and Zn & Cd doped CuO films show polycrystalline nature with face centered cubic structure. Also, Zn& Cd doping radically increases the crystalline and changes the crystallite size. SEM images illustrate that the surface morphology was formed by grains which are rod shaped grains uniformly distributed. The transmittance of the prepared CuO films recorded in the UV visible spectra show 40 to 70% in the visible region. The estimated optical band gap values are blue shifted in Zn doped CuO thin films. Hall measurement shows that the films are n-type semiconductor. Also, it is experiential that when the Cd doped, the electrical resistivity is high when compared to Zn doped CuO thin films.